Proposal for Optimizing Specific Distribution Routes by Means of the Specific Method of Operational Analysis - Kampf, Rudolf; Hlatka, Martina; Savin, Gleb (Communications - Scientific letters of the University of Zilina, 2017)
The paper focuses on the issue of optimizing material collection and distribution routes in the restrictive parameters. In the article, Clarke-Wright method was used, where the restricting parameters are vehicle capacity, vehicle speed and compliance with the social legislation related to the work of vehicle crew. The research aimed at the collection and distribution of steel components within a particular company. For the optimization, the data of weekly collection and distribution were used. By the Clarke-Wright method application, time savings of 40% of the vehicle use were achieved.